2020
DOI: 10.1111/jdi.13317
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for new‐onset diabetes mellitus after kidney transplantation: A systematic review and meta‐analysis

Abstract: Aims/Introduction: To systematically review the risk factors for new-onset diabetes mellitus after kidney transplantation, and to provide a theoretical basis for the prevention and management of new-onset diabetes mellitus after kidney transplantation. Materials and Methods: We searched PubMed, Web of Science, Embase, the Cochrane Library databases and other databases for case-control studies related to risk factors for newonset diabetes mellitus after kidney transplantation published between January 2005 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…While the traditional risk factors for DM also apply to PTDM, some specific risk factors about the transplant procedure can additionally increase the risk for PTDM [ 6 ]. In a recent systematic review and meta-analysis of 24 case–control studies, Xia et al [ 8 ] have identified advanced age, body mass index, family history of diabetes, tacrolimus use, history of hypertension, polycystic kidney disease, acute rejection, hepatitis B virus infection, and hepatitis C virus infection as risk factors for PTDM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the traditional risk factors for DM also apply to PTDM, some specific risk factors about the transplant procedure can additionally increase the risk for PTDM [ 6 ]. In a recent systematic review and meta-analysis of 24 case–control studies, Xia et al [ 8 ] have identified advanced age, body mass index, family history of diabetes, tacrolimus use, history of hypertension, polycystic kidney disease, acute rejection, hepatitis B virus infection, and hepatitis C virus infection as risk factors for PTDM.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the intense research on the pathophysiology and risk factors for PTDM [ 8 , 9 ], it is still unclear how this complication impact patient outcomes. Some studies have reported no impact of PTDM on patient and graft survival [ 10 – 14 ] while others indicate that mortality and graft failure is significantly increased with PTDM [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a meta-analysis that included 21 retrospective observational studies with a patient sample size of 241,381, obese recipients showed a higher risk of having biopsy-proven acute rejection and delayed graft function, compared with their healthy BMI counterparts [ 49 ].…”
Section: Morbidity and Mortality In Patients With Obesity After Kidney Transplantationmentioning
confidence: 99%
“…Obesity may increase the risk of cardiovascular complications, DM, and metabolic syndrome, which are well-known posttransplant complications related to the chronic use of immunosuppression[ 4 - 9 ]. However, data on the clinical outcomes of kidney transplantation in obese patients are conflicting due to the lack of consensus on a commonly accepted definition of obesity and on a standard approach to obesity assessment[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the clinical outcomes of kidney transplantation in obese patients are conflicting due to the lack of consensus on a commonly accepted definition of obesity and on a standard approach to obesity assessment[ 3 ]. Most transplant centers incorporate interventions aiming to target obesity in kidney transplant candidates, including dietary education and lifestyle modifications[ 3 - 9 ]. For those failing nutritional restriction and medical therapy, bariatric surgery has recently emerged as a valid therapeutic approach for improving access to kidney transplantation as well as posttransplant outcomes.…”
Section: Introductionmentioning
confidence: 99%